Weaning : What to Feed, When to Feed, and How to Feed Your Baby - Karmel, Annabel (London Dorling Kindersley, 2010)
A guide to weaning your baby. It guides you through various aspects of weaning your baby. It starts at the very beginning with basic, but crucial details, such as what type of spoon to use and the time of day to first offer solids, and covers other common concerns like when to begin weaning, fussy eaters and allergy advice.
Including Illustrations and Index
Keywords: Baby foods -- Infants--Weaning